2001
DOI: 10.1542/peds.107.3.e32
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Temporal Variations in the Prevalence of Heart Defects

Abstract: ABSTRACT. Background. Documenting the prevalence and trends of congenital heart defects provides useful data for pediatric practice, health-care planning, and causal research. Yet, most population-based studies use data from the 1970s and 1980s. We sought to extend into more recent years the study of temporal and racial variations of heart defects occurrence in a well-defined population.Methods. We used data from the Metropolitan Atlanta Congenital Defects Program, a population-based registry with active case … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
367
10
7

Year Published

2005
2005
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 517 publications
(420 citation statements)
references
References 20 publications
29
367
10
7
Order By: Relevance
“…We25 and others26 have reported the constraints of administrative data sets for detection and categorization of ACHD. Even so, ICD‐9 codes have been used to investigate CHD‐related births and mortality in the United States 27, 28. TOF accounted for the largest number of HF hospitalizations in this study, consistent with prior studies reporting HF as the most common cause of hospitalization in this group 29.…”
Section: Discussionsupporting
confidence: 83%
“…We25 and others26 have reported the constraints of administrative data sets for detection and categorization of ACHD. Even so, ICD‐9 codes have been used to investigate CHD‐related births and mortality in the United States 27, 28. TOF accounted for the largest number of HF hospitalizations in this study, consistent with prior studies reporting HF as the most common cause of hospitalization in this group 29.…”
Section: Discussionsupporting
confidence: 83%
“…37 In addition, birth defects registries that only ascertain cases of birth defects in the first year of life exclude infants who died shortly after birth without an autopsy, or diagnosed later in childhood. Moreover, our study only includes live births, whereas other studies 8,12 include data on stillbirths and terminations. Without medical record review, the FBDR data also lack information on case confirmation or case severity.…”
Section: Original Articlesmentioning
confidence: 99%
“…The main reasons for fetal karyotyping were categorized as described by Kessler et al 6 The patients were classified according to the number of major and minor sonographic markers observed before and after puncturing for fetal karyotyping in accordance with Raniga et al 7 Abnormalities identified through imaging studies performed during prenatal care were also classified as single or multiple defects, in accordance with Staebler et al, 8 before and after performing fetal karyotyping. To determine the congenital heart defect observed, we used the classification suggested by Botto et al 9 The Kaplan-Meier test was used to construct the survival curve, by means of the BioEstat 5.0 software.…”
Section: Objectivementioning
confidence: 99%